Sistem Pembelajaran Pendidikan Agama Islam dalam Setting Inklusif di SDN Lemahputro 1 Sidoarjo - Hamidah, Ani Mar'atul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2015)
The article describes and explores the Islamic education learning system withininclusive setting. The data were collected through observation, interview, anddocumentation. The results show the combination of components as neatlyand organizingly to gain ends. First stage is screening students throughidentification, assesment, and curriculum modification. The teacher of Islamiceducation modified RPP to inclusive program. The Islamic education learningsystem within inclusive setting for students with special needs is so flexible thatfits the condition and characteristic of the students. Furthermore, input learningwas processed with professional teachers, good infrastructures, and the rightenvironment. Therefore, the expected output was gained.